Bartolov Al Araf in "nacionalno vprašanje" - Virk, Tomo (Primerjalna književnost, 2012)
This article focuses on the issue of the "nationalist" interpretation of Vladimir Bartol's 1935 collection of short stories Al Araf. Relying extensively on the manuscripts from his estate and published documentation, it seeks to prove that this issue does not have any unilateral answers. The commonly held impression is that while writing his collection Bartol treated the ethnic issue solely as one of the many ideas he experimented with in his stories. This was also how his contemporaries understood him at that time. However, more recent, "nationalist" interpretations can nonetheless find firm support in Bartol's postwar self-explanation and especially in the fact that the writer's novellas thematized the type of subjectivity that Slovenians needed to carry out great historical changes and in some way predicted these changes.
Keywords: Bartol, Vladimir, 1903-1967; književnost; literature; družba; society; Slovene literature; slovenska književnost; narodnostno vprašanje; TIGR; literarna interpretacija